-4c+9(3c+5)=

Simple and best practice solution for -4c+9(3c+5)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4c+9(3c+5)= equation:


Simplifying
-4c + 9(3c + 5) = 0

Reorder the terms:
-4c + 9(5 + 3c) = 0
-4c + (5 * 9 + 3c * 9) = 0
-4c + (45 + 27c) = 0

Reorder the terms:
45 + -4c + 27c = 0

Combine like terms: -4c + 27c = 23c
45 + 23c = 0

Solving
45 + 23c = 0

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-45' to each side of the equation.
45 + -45 + 23c = 0 + -45

Combine like terms: 45 + -45 = 0
0 + 23c = 0 + -45
23c = 0 + -45

Combine like terms: 0 + -45 = -45
23c = -45

Divide each side by '23'.
c = -1.956521739

Simplifying
c = -1.956521739

See similar equations:

| 10p+18=-12 | | 13q+48=-3q | | -12(-5c-6)= | | 6+5(-3a+8)=136 | | -2=1n+2 | | 2x^4+2x^3+x^2=656 | | x-2(6.5+3.5x)=11 | | -9(5+2f)= | | -5x-7x+3+6= | | 2x-39=21 | | 8t+1=-7 | | 3(-12)-6=42 | | 50=x+y*2x | | 9-4z=1 | | -3x+8=56+5x | | -19=19+19b | | X+124+x+74=180 | | 1.25-7=53.1 | | 3(16)-6=42 | | 4x+34+90=3x | | x-3+10+x-10+2+8= | | 6+2d=18 | | -5(8+4d)-9d= | | 168=-8(4m+7) | | 0=xsin(0.5x)-2cos(0.5x) | | 6x+2=42 | | 3(x-6)=6x+24 | | 4n-14=82 | | 1+4y=9 | | 3u-6=-42 | | 9x=-60 | | 3x+2+6x-13=5x |

Equations solver categories